2018
DOI: 10.7554/elife.36806
|View full text |Cite
|
Sign up to set email alerts
|

NK cells inhibit Plasmodium falciparum growth in red blood cells via antibody-dependent cellular cytotoxicity

Abstract: Antibodies acquired naturally through repeated exposure to Plasmodium falciparum are essential in the control of blood-stage malaria. Antibody-dependent functions may include neutralization of parasite–host interactions, complement activation, and activation of Fc receptor functions. A role of antibody-dependent cellular cytotoxicity (ADCC) by natural killer (NK) cells in protection from malaria has not been established. Here we show that IgG isolated from adults living in a malaria-endemic region activated AD… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
110
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(115 citation statements)
references
References 37 publications
5
110
0
Order By: Relevance
“…NK cell‐mediated ADCC has been well recognized through its implication in the killing of tumor cells and virus‐infected cells. A recent study has provided evidence that NK cells can inhibit Plasmodium falciparum by lysing infected red blood cells via ADCC . This finding highlights the importance of NK cells in boosting adaptive immunity, not only to control viral infections but also parasites.…”
Section: Nk Cell Receptorsmentioning
confidence: 87%
“…NK cell‐mediated ADCC has been well recognized through its implication in the killing of tumor cells and virus‐infected cells. A recent study has provided evidence that NK cells can inhibit Plasmodium falciparum by lysing infected red blood cells via ADCC . This finding highlights the importance of NK cells in boosting adaptive immunity, not only to control viral infections but also parasites.…”
Section: Nk Cell Receptorsmentioning
confidence: 87%
“…PfEMP1 variants containing domains of the CIDRα1 class generally bind to EPCR on endothelial cells and are associated with severe malaria (10), whereas variants containing domains of the CIDRα2-6 classes bind to CD36 present on several host cell types, including microvascular endothelial cells, mononuclear phagocytes, and platelets (16, 37). Antibodies targeting these PfEMP1 domains can potentially disrupt adhesion of IEs to host receptors but can also facilitate IE clearance via opsonization and phagocytosis or antibody-mediated cytotoxicity (10, 38, 39). Consistent with a prior study conducted in a Tanzanian cohort (28), we observed early acquisition of IgG antibodies against EPCR-binding PfEMP1 variants of the CIDRα1 domain class relative to CD36-binding variants in both age-stratified cross-sectional and longitudinal analyses.…”
Section: Discussionmentioning
confidence: 99%
“…There is little evidence that antibodies to infected erythrocytes stimulate monocytes or neutrophils to produce antibody‐dependent respiratory burst, in contrast to antibody‐dependent respiratory burst following ingestion of opsonized merozoites (discussed earlier). Antibodies toward infected erythrocytes can also activate natural killer cells, resulting in degranulation and cytokine production, leading to parasite lysis and growth inhibition . Antibody‐dependent interactions with natural killer cells by infected erythrocytes are dominated by a subset of cells called adaptive natural killer cells .…”
Section: Functional Antibody In Malariamentioning
confidence: 99%